Définition de indices climatiques pour l’évaluation du changement climatique en acte: une étude effectuée en Piémont (NO Italie) - FRATIANNI, SIMONA; ACQUAOTTA, FIORELLA (Vinet F., 2008)
The analysis of the historical thermal-pluviometric series of Piedmont in the 1951-2000 period provided experts with the main climate trends. In order to better understand the consequences of climate variations on our society, we have calculated the climatic indexes (frost days, days with no thaw, tropical days, rainy days, density of precipitations) over the whole period and over WMO 30-year periods (1951-80, 1961-90, 1971-2000). Also the use of thermograms, pluviometric regimes, and ombrothermal diagrams underlined differences among the three 30-year periods. Furthermore, the North Atlantic Oscillation enabled experts to determine some dry or hydric surplus periods that are closely connected with the Polar Vortex activity. The indexes used have emphasized some anomalous periods that have been used to define possible scenarios.